Pengaruh Asap Cair Sabut Pinang (Areca catechu L) Terhadap Kadar Protein Udang (Crustacae) yang Disimpan pada Suhu 50C - Faratika Agustin; Iryani Iryani; Isniyetti Isniyetti (Departemen Kimia FMIPA UNP, 2012)
A study on the effect of liquid smoke fibrous shell of areca nut (Areca catechu L) the protein content of shrimp stored at a temperature of 50oC. The purpose of this study was to see the effect of liquid smoke concentration and length of storage the protein content of shrimp. This study begins with shrimp dipping into different concentrations and stored with variety and storage time of shrimp used as control without giving liquid smoke. Observations made ​​during the 15 days of the smell, color, texture and protein content of shrimp. Shrimp protein content determined by the method of Lowry. Based on the results of the study can be seen a decline in the quality of the shrimp as changes in odor, color and texture. From the results of the determination of the protein content of shrimp with giving liquid smoke have a higher protein content when compared to the shrimp without giving of liquid smoke. Liquid smoke concentration and sample storage time best in this study was 15% liquid smoke concentration with storage time 3 days.